Valence and Rydberg excitations of 2-fluorotoluene in the 4.4–10.8 eV photoabsorption energy region. (July 2023) - Randi, P.A.S.; Kumar, S.; Lozano, A.I.; Bettega, M.H.F.; Hoffmann, S.V.; Jones, N.C.; Barbosa, A. Souza; Limão-Vieira, P.
Highlights: 2-fluorotoluene vacuum ultraviolet photoabsorption spectrum. Absolute cross-section values in the photon energy range 4.4–10.8 eV. Electronic state spectroscopy of valence and Rydberg excitations. Theoretical calculations at time dependent density functional theory level. Photolysis rates in the Earth's atmosphere (0–50 km). Abstract: The electronic state spectroscopy of 2-fluorotoluene in the gas phase has been investigated for the first time using high-resolution vacuum ultraviolet photoabsorption experiments in the 4.4–10.8 eV energy-range, with absolute cross-section measurements obtained. Additionally, we also present a novel set of ab initio calculations (vertical excitation energies and oscillator strengths) at two different levels of theory, equation-of-motion coupled-cluster singles and doubles (EOM-CCSD) and time-dependent density functional theory (TD-DFT). These are used in the assignment of valence, mix valence-Rydberg and Rydberg transitions, with the associated vibronic series analysed. The measured absolute photoabsorption cross-sections have been used to calculate the photolysis lifetime of 2-fluorotoluene in the Earth's atmosphere.